MASS MEDIA AS WEAPONS IN CONTENDING TERRORISM IN NIGERIA - Oju, Enakeno Victoria (UI Scholars Hub, 2023)
Terrorism has been of global concern in recent times. The problem is not only a great challenge and a threat to the security and stability of a nation; it hampers overall growth and development. In spite of government’s counter-terrorism interventions and responses, as well as interventions from other nations and bodies, the issue of terrorism in Nigeria appears to be rising, which calls for more holistic approaches in tackling the menace. This study is an attempt to contribute to the ongoing interventions to combat the current challenge of terrorism, particularly the Boko Haram insurgency in Nigeria. The paper, therefore, attempts to expose and explore various ways the media can be used to instigate a radical transformation towards curtailing terrorism and achieving a terrorism-free state. The study adopts the action research method as a research methodology. It is also predicated on the Agenda-setting theory as well as the cultivation theory. Findings from this study reveal that the aim of terrorists is to create insecurity, destabilise the country to make it ungovernable. This study thus in examining the power of the mass media in the curtailing of terrorism concludes that the mass media are lethal weapons for contending terrorism.